A norm equivalence for the mixed norm of Fock type. Issue 12 (1st December 2016) - Ha, Jeong Min; Cho, Hong Rae; Lee, Han-Wool
Abstract : In this paper, we prove that the mixed norm for an exponential type weighted integral of an entire function is equivalent to the mixed norm of its radial derivative and the distortion function from the weight function in the n -dimensional complex space.